Connected Vessels: West Asia and East Asia in China’s Geopolitics / Vasijas conectadas: Asia Occidental y Asia Oriental en la Geopolítica de China - Shichor, Yitzhak (Araucaria, 2016)
East Asia and West Asia (the Middle East)2 are usually treated in the academicliterature as two distinct and separate issues in Chinese foreign policy. Studies ofChina’s policy in East Asia hardly mention the Middle East and studies of theMiddle East hardly mention East Asia. In fact, these two regions are not simplyinterconnected in China’s geopolitical outlook but provide clues to understandingBeijing’s foreign policy toward each of them –they are interdependent. As such,they are connected vessels in the sense that the situation in one region affects,or even determines, China’s policy in the other. This is evident in a number ofperspectives: strategy, economics, energy, military and Islam. Mutual dependenceis one of the features of contemporary international relations, after the end of theCold War. While usually it is limited to one aspect or two (primarily economic andmilitary), in the case of China and the Middle East, mutual regional dependenceinvolve a number of levels.